Students' Performance and Perceptions of Flipped Classroom Approach in Business Mathematics - Bhatta, Narayan Datta (Journal of Durgalaxmi, 2025)
The Flipped Classroom is an innovative instructional approach increasingly adopted in higher education for promoting higher-order thinking and problem-solving. It combines individualized pre-class learning through online lecture videos with in-class collaborative activities guided by instructors. Despite its global adoption, this model remains underexplored in Nepalese higher education institutions (NHEIs). This case study examined the learning outcomes and student perceptions of the flipped approach over four weeks in a Business Mathematics class of 40 students at a Far Western University Campus. Data were collected through a test, a student survey, and a focus group discussion with six purposively selected students. Descriptive and qualitative analysis indicated improved student performance and positive perceptions. Students reported enhanced understanding, problem-solving skills, and development of digital and social competencies. They also considered the approach suitable for digital-era learners and expressed interest in applying it to other courses. Key factors identified for successful implementation included adequate digital infrastructure, skilled educators, motivated students, and clear, high-quality lecture videos. The study highlights the potential of the flipped model to improve teaching and learning in NHEIs and encourages university administrators and educators to adopt it for quality education. It also calls on scholars to explore the model further, addressing existing research gaps and ensuring broader, more generalizable findings through extended studies.